Pembelajaran Berbasis Multimedia Interaktif Mahasiswa Di Perguruan Tinggi - Karim, Bisyri Abdul; Ansar, Ansar (Universitas Muslim Indonesia, 2022)
This study examines the interactive multimedia-based learning of students in higher education. The method used in this research study is library research. The procedure of this research using the stages of library research include; (1) selecting study topics, (2) exploring information, (3) formulating the focus of writing, (4) collecting data sources, (5) preparing data presentations, and (6) compiling reports in the form of research journal descriptions. This research data collection technique relies on documentation sources by exploring sources related to the focus of the problem being studied. data analysis technique uses content analysis to obtain the substance from appropriate and verifiable references based on the source through the stages of sorting and comparing various definitions and opinions from existing literature sources to achieve the suitability of relevant sources.The results of the analysis of this study can be concluded that; First, learning is an important process that greatly determines behavior change and improvement. In the context of higher education learning, lecturers are required to be more adaptive to various learning tools or media. Learning in higher education will be more interesting by using learning media. Second, learning media plays a very effective role. One type of this media is interactive multimedia whose contents combine various forms of media such as text, audio, and video to make it easier for students to use it in learning. Lecturers must be more innovative in using this interactive multimedia and must be skilled at technological developments.